Efficient Approach to LVRT Capability of DFIG-Based Wind Turbines under Symmetrical and Asymmetrical Voltage Dips Using Dynamic Voltage Restorer - Kiarash Azizi; Murtaza Farsadi; Mohammad Farhadi Kangarlu (International Journal of Power Electronics and Drive Systems (IJPEDS), 2017)
The capability of low-voltage ride-through (LVRT) of doubly fed induction generator (DFIG) has been considered as an essence for grid code requirements. Any unbalance on the grid side causes the rotor current of the generator to rise which leads to saturate the dc-link of the back-to-back converter or even destroy it. To meet this requirement, a dynamic voltage restorer (DVR) without dc-link energy storage elements is utilized to compensate any disturbance imposed to the DFIG wind turbine system. On the time of any disturbance or fault, DFIG and DVR are properly controlled in order to compensate the specified faulty phase uninterruptedly. DVR is connected in series to the grid and by injecting instantaneous compensating voltage, prevents the stator voltage from rapid changing; consequently, the rotor side converter can accomplish its normal operation. As voltage dips are the most common grid faults subjected to DFIGs, this paper investigates both symmetrical and asymmetrical voltage dips caused by grid faults. The independent and instantaneous phase voltage compensation, less volume, weight, and cost are the merits to utilize the proposed DVR along with DFIG wind turbines. PSCAD/EMTDC based simulations verifies the capabilities of the proposed technique for the LVRT capability of DFIG.